(untitled) (JISTECH: Journal of Information Science and Technology, 2024)
The selection of PAR chairpersons at the Sanggeng Zion Congregational Bible Christian Church is still relatively manual, for this reason this study aims to create a decision-making system for selecting PAR chairpersons based on existing criteria. This study uses the WEIGHTED PRODUCT method with stages, namely each criterion is ranked based on the level of importance. Then given a weight so that the normalized value can be calculated. In order to evaluate the expected alternatives, single attribute utilities are calculated so that the resulting output is a decision support system in the form of a ranking with the order of the greatest value. This application is designed using the PHP and MySQL programming languages. The results obtained from this study were Sister Thersia Makabori becoming Chair of the PAR with the highest score of 0.24 to be recommended as Chair of the PAR at GKI Sion Sanggeng Manokwari based on the criteria that met the highest score.